Demonstration of an E-mailed Worksite Nutrition Intervention Program - Gladys Block; Torin Block; Patricia Wakimoto; Clifford H. Block (Centers for Disease Control and Prevention, 2004)
Introduction Dietary fat and low fruit and vegetable intake are linked to many chronic diseases, and U.S. population intake does not meet recommendations. Interventions are needed that incorporate effective behavior-change principles and that can be delivered inexpensively to large segments of the population. Methods Employees at a corporate worksite were invited to participate in a program, delivered entirely by e-mail, to reduce dietary fat and increase fruit and vegetable intake. Behavior-change principles underlying the intervention included tailoring to the participants dietary lifestyle, baseline assessment and feedback about dietary intake, family participation, and goal setting. Assessment, tailoring, and delivery was fully automated. The program was delivered weekly to participants e-mail inboxes for 12 weeks. Each e-mail included information on nutrition or on the relationship between diet and health, dietary tips tailored to the individual, and small goals to try for the next week. In this nonrandomized pilot study, we assessed technical feasibility, acceptability to employees, improvement in Stage of Change, increase in fruit and vegetable consumption, and decrease in fat intake. Results Approximately one third (n = 84) of employees who were offered the 12-week program signed up for it, and satisfaction was high. There was significant improvement in Stage of Change: 74% of those not already at the top had forward movement (P < .001). In addition, results suggest significant increase in fruit and vegetable consumption (0.73 times/day, P < .001) and significant decrease in intake of fat sources (-0.39 times/day, P < .001). Conclusion This inexpensive program is feasible and appears to be effective. A randomized controlled trial is needed.